Clinical Efficacy of Various Diagnostic Tests for Small Bowel Tumors and Clinical Features of Tumors Missed by Capsule Endoscopy - Jung Wan Han; Sung Noh Hong; Hyun Joo Jang; Seong Ran Jeon; Jae Myung Cha; Soo Jung Park; Jung Sik Byeon; Bong Min Ko; Eun Ran Kim; Hwang Choi; Dong Kyung Chang (Gastroenterology Research and Practice)
Background. We aimed to evaluate the efficacy of various diagnostic tools such as computerized tomography (CT), small bowel follow-through (SBFT), and capsule endoscopy (CE) in diagnosing small bowel tumors (SBTs). Additionally, we aimed to evaluate the clinical features of SBTs missed by CE. Methods. We retrospectively studied 79 patients with histologically proven SBT. Clinical data were analyzed with particular attention to the efficacy of CT, SBFT, and CE in detecting SBT preoperatively. We also analyzed the clinical features of SBTs missed by CE. Results. The most common symptoms of SBT were bleeding (43%) and abdominal pain (13.9%). Diagnostic yields were as follows: CT detected 55.8% of proven SBTs; SBFT, 46.1%; and CE, 83.3%. The sensitivity for detecting SBTs was 40.4% for CT, 43.9% for SBFT, and 79.6% for CE. Two patients with nondiagnostic but suspicious findings on CE and seven patients with negative findings on CE were eventually found to have SBT. These nine patients were eventually diagnosed with gastrointestinal stromal tumor (4), small polyps (3), inflammatory fibroid polyp (1), and adenocarcinoma (1). These tumors were located in the proximal jejunum (5), middle jejunum (1), distal jejunum (1), and proximal ileum (1). Conclusion. CE is more efficacious than CT or SBFT for detecting SBTs. However, significant tumors may go undetected with CE, particularly when located in the proximal jejunum.